2016
DOI: 10.1074/jbc.m115.699728
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Dimer Reversible Dissociation

Abstract: Tubulins are evolutionarily conserved proteins that reversibly polymerize and direct intracellular traffic. Of the tubulin family only ␣␤-tubulin forms stable dimers. We investigated the monomer-dimer equilibrium of rat brain ␣␤-tubulin using analytical ultracentrifugation and fluorescence anisotropy, observing tubulin in virtually fully monomeric and dimeric states. Monomeric tubulin was stable for a few hours and exchanged into preformed dimers, demonstrating reversibility of dimer dissociation. Global analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…No detection of the dimer here could be an artifact from the detection limit of the instrument or could be due to slow binding on‐rate of Cdh23 EC1‐2 (WT) toward dimerization . Moreover, it is well documented that the K D obtained from SV or SE varies widely for the same proteins and these variations are mainly attributed to the differences in internal pressure in AUC cell arising from different run‐time .…”
Section: Resultsmentioning
confidence: 97%
“…No detection of the dimer here could be an artifact from the detection limit of the instrument or could be due to slow binding on‐rate of Cdh23 EC1‐2 (WT) toward dimerization . Moreover, it is well documented that the K D obtained from SV or SE varies widely for the same proteins and these variations are mainly attributed to the differences in internal pressure in AUC cell arising from different run‐time .…”
Section: Resultsmentioning
confidence: 97%
“… 2 , 3 , 4 Studies on the thermodynamic and kinetic stability of -tubulin heterodimers, which ultimately impacts the assembly and stability of microtubules, have produced a broad range of binding affinities and kinetics, ranging over 5 orders of magnitude from 10 −11 to 10 −6 M, with dissociation rates from 10 −5 to 10 −2 s −1 . 5 , 6 , 7 , 8 , [9] The variation in previous results can be attributed to a combination of various technical reasons and to biochemical differences between tubulins from different species. 10 To achieve the required sensitivity, many single-molecule studies have had to rely on labelling and although care was taken to ensure that tubulin was not damaged by labelling, a quick, simple, label-free method is desirable because it excludes any potential perturbations.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, it has been shown that purified ␣␤-tubulin, i.e. protein obtained postfolding and postdimerization, reversibly dissociates to native monomers, and these free monomers can exchange into added tubulin, reversibly forming new ␣␤ dimers (13). This study and nearly all previous studies of tubulin dimer dissociation have used tubulin isolated from mammalian brain (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 92%
“…protein obtained postfolding and postdimerization, reversibly dissociates to native monomers, and these free monomers can exchange into added tubulin, reversibly forming new ␣␤ dimers (13). This study and nearly all previous studies of tubulin dimer dissociation have used tubulin isolated from mammalian brain (13)(14)(15)(16)(17)(18)(19). Tubulin from brain is heterogeneous in its composition of ␣ and ␤ isotypes (20,21) and is subject to many types of post-translational modifications that can modulate the protein's in vitro behavior (22).…”
mentioning
confidence: 98%